On the solution of the problem of synthesis of the control system for the process of dosed feed of electrode wire for arc welding equipment - Lebedev, V.A. (Electrical Engineering & Electromechanics, 2021)
Goal. Refinement of the methodology for the development of an effective control system for an electric drive with controlled relay-type regulators for organizing a metered feed of an electrode wire using the parameters of the arc process with the possibility of using it in design practice and practice of technological application. Methodology. The proposed method for the mathematical description (mathematical model) of the system of the developed structure electric drive - arc process with current feedback of welding with a variable structure device is based on the theory of automatic control as applied to nonlinear elements, the application of the theory of operational calculus. At the same time, a selection and description of a nonlinear node in the feedback circuit in the form of a relay element with a certain structure and subsequent linearization of this element was made. As an electric motor of the electrode wire feeder, a new development of a specialized valve electric motor is used, which is used in the system with a microprocessor controller. Results. Due to the presence of a substantially nonlinear link, the calculation of the valve electric drive system – the arc process can be found on the basis of a system of nonlinear differential equations, which is practically impossible for practical application. In this work, these complications are overcome on the basis of a rational choice of the description of the nonlinear link, its harmonic linearization and obtaining on this basis a mathematical description of the system, from which, using the methodology of operational calculus, the relations necessary for calculating the parameters of the system are determined in analytical form. Originality. The problem of calculating a rather complex problem of mathematical description of the valve electric drive system – a technological link in the form of an arc process with a substantially nonlinear link in the feedback circuit in the work is solved with the effective use of a set of methodological methods, which include as a means of representing individual links, including nonlinear links selected simplifications and solutions of the obtained differential equations using original methods of operational calculus. The proposed method (mathematical model) is tested in two directions – oscillography of a real system, as well as system simulation. Practical significance. Using the developed methods for describing the control system, it is possible to calculate its characteristics and, on their basis, select the parameters for setting the electric drive controller, which allows, without additional experimental research, to obtain the necessary character of the transfer of electrode metal, and, consequently, the quality of the result of the arc process.